The effect of high concentration of molibdenium and zinc on the growth of the strain thermodesulfovibrio sp. V2 from the deep terrestrial biosphere; Перспективы развития фундаментальных наук; Т. 4 : Биология и фундаментальная медицина - Klimova K. M. (2017, 2017)
Заглавие с экрана